Penerapan Metode Prophetic Parenting Terhadap Pola Asuh Anak Di Madrasah Ibtidaiyah Adab Baleharjo - Kumalasari, Putri; Wahyuningsih, Diah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of the research conducted is to understand the application of the prophetic parenting method to the parenting patterns at Mi Adab Muhammadiyah Baleharjo and the involvement of parents and teachers in the implementation of the prophetic parenting method. The research uses a qualitative method with data collection through literature review, interviews, and field studies. In the research findings, it was discovered that in the implementation of the prophetic parenting method in child-rearing at MI Adab Baleharjo, there is a reciprocal relationship between teachers and parents in applying the prophetic parenting method. Based on the research findings, it can be concluded that the implementation of the prophetic parenting method in child-rearing at MI Adab Baleharjo is in accordance with the teachings of the Prophet Muhammad (peace be upon him), and this has become the main guideline for the school in the effort to educate children both at school and at home.